Peranan Koperasi Mina Segara Dana dalam Meningkatkan Usaha Garam Beryodium di Desa Kusamba Kecamatan Dawan Kabupaten Klungkung Provinsi Bali - LILI EFNITA; I GEDE SETIAWAN ADI PUTRA; I GEDE BAGUS DERA SETIAWAN (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2022)
The Roles of Mina Segara Cooperative in Improving Iodized Salt Farming in Kusamba Village, Dawan District, Klungkung Regency, Bali Province. The definition of cooperative according to Law 25/1992 on cooperative is a business entity that acts as a driving force for the people's economy with the principle of kinship. The Mina Segara Cooperative, located in Kusamba Village, is a cooperative that acts as a production unit of iodized salt through the Uyah Kusamba program. This study aims to determine the roles of the Mina Segara Dana Cooperative in improving the iodized salt farming in Kusamba and the economic and social impacts of the cooperative for salt farmer families. This research is quantitative research with a descriptive analysis method. Data were collected by distributing questionnaires and through in-depth interviews. The results show that the roles of the cooperative include determining the purchase price, organizing standardized packaging of products, and helping promotion. The cooperative also facilitates government extension programs for salt farmers. Mina Segara Cooperative must be able to take advantage of online media as a new promotional medium to expand the market and increase sales.